2010
DOI: 10.3109/14992020903397838
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of computer-based auditory training for adult users of cochlear implants

Abstract: Cochlear implantation is effective at restoring partial hearing to profoundly deaf adults, but not all patients receive equal benefit. The present study evaluated the effectiveness of a computer-based self-administered training package that was designed to improve speech perception among adults who had used cochlear implants for more than three years. Eleven adults were asked to complete an hour of auditory training each day, five days a week, for a period of three weeks. Two training tasks were included, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 25 publications
3
82
1
Order By: Relevance
“…These are important issues for cochlear-implant users because they find listening to speech in noisy environments difficult (Turner et al, 2004), and visual speech information has been shown to improve performance (Kaiser, Kirk, Lachs, & Pisoni, 2003;Grant, Walden, & Seitz, 1998). Previous research suggests that computer-based auditory training can improve speech perception amongst people with implants (Fu, Galvin, Wang, & Nogaki, 2005;Stacey et al, 2010;Ingvalson, Lee, Fiebig, & Wong, 2013), and it is also possible they would benefit from training to locate speakers in a multi-talker array.…”
Section: Discussionmentioning
confidence: 99%
“…These are important issues for cochlear-implant users because they find listening to speech in noisy environments difficult (Turner et al, 2004), and visual speech information has been shown to improve performance (Kaiser, Kirk, Lachs, & Pisoni, 2003;Grant, Walden, & Seitz, 1998). Previous research suggests that computer-based auditory training can improve speech perception amongst people with implants (Fu, Galvin, Wang, & Nogaki, 2005;Stacey et al, 2010;Ingvalson, Lee, Fiebig, & Wong, 2013), and it is also possible they would benefit from training to locate speakers in a multi-talker array.…”
Section: Discussionmentioning
confidence: 99%
“…As CI users' understanding of pitch and timbre information with their implant improves, music appreciation may also improve as the stimulation patterns become more familiar. We find it interesting that active speech training has been shown to improve CI users' speech perception even after years of experience with their device (see, e.g., , 2008Stacey et al, 2010). Given the substantial improvements in MCI performance with MCI training observed in previous studies with adult English-speaking CI users (Galvin et al, , 2012, it is possible that similar training may also improve Mandarin-speaking CI users' music perception.…”
mentioning
confidence: 92%
“…Although in the present article we focus on training using clear auditory feedback, which cannot be used to train postlingually deafened cochlear implant users, Davis and colleagues (2005) demonstrated that written feedback is as effective as auditory feedback, and the efficacy of written feedback has been demonstrated for rehabilitating recently implanted cochlear implant (CI) users (Stacey et al, 2010). The training method we choose to apply involves providing listeners with a clear instance of a word, followed by its noise-vocoded equivalent.…”
mentioning
confidence: 99%